The Impact of the Crisis on the Homeless: Breaks and Continuities in the Context of Change. The Case of Biscay (Bizkaia) - Moreno Márquez, Gorka (Cuadernos de Trabajo Social, 2013)
This article seeks to delve into the impact the current economic and social crisis is having on the homeless. To this end, the results of two studies are presented. The first was done before the crisis and the second at the present time and both have been analyzed in the comparative key. As a consequence of the crisis, an increase in the number of homeless people has been detected. Although some characteristics of the group have remained constant, others have changed. Difficulties in accessing the labor market and cuts in certain economic benefits are increasing the duration of social incorporation processes. This context is causing the personal situation of homeless people to worsen, especially in areas such as mental disorders or consumption of drugs. The immigrant community is the one that is suffering this impact the most. This situation shows the need to reflect on the care of the homeless and to rethink the way professionals intervene, especially at a critical time like this.